Proposed Strategy Formulation of PT Jelajah Alam Raya Komunitas (The Indonesian Journal of Business Administration, 2014)
Abstract. Increasing GDP for next decade will lead to increasing Indonesian middle class. It effected the growing of business travel in Indonesia. Based on data from World Travel and Business Council, Oxford Economics, 2013 Indonesia one the biggest contributor demand for business travel in the next 10 years. Indonesian travel market growth estimate in 2012 until 2020 is about 5.9 % per year. Based on the financial performance, JAR Travels have unhealthy financial condition, due to the actual revenue didn’t meet the target revenue. This condition resulted the target Break Even Point for one year is not reached. To get the problem solving of issues that occurred, the analysis strategy and proposed strategies will be discussed in this journal. The environmental scanning for external and internal are conducted to find the root cause. External scanning is done by using the PEST, Five Forces, Collaborator Analysis and Competitor Analysis. The internal scanning is done by using value chain tools. The results of the external and internal analysis is used to obtain directional strategy, proposed business strategy, and to generate functional strategy.From the analysis, JAR Travels is proposed to implement several strategy to achieve target revenue and BEP. The proposed of directional strategy is stability strategy with market penetration. Proposed business strategy is "Differentiation Focus". The proposed functional strategy are increasing online travel service by the build system, increasing capability in IT, maximizing online marketing, Increasing the function of HR, maximizing control in finance, increasing partnerships to support JAR Travels business, change distribution channels, create uniqueness products as competitive advantages, and market penetration to grab the opportunity.Keywords: strategic formulation, online travel community, business strategy